2018
DOI: 10.1016/j.jsat.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

The association between impulsivity, emotion regulation, and symptoms of alcohol use disorder

Abstract: Emotion dysregulation and impulsivity are important factors influencing the development and course of alcohol dependence. However, few empirical studies investigate the association between different aspects of impulsivity (cognitive, attentional, behavioral), emotion regulation, and alcohol use disorder symptoms in the same model. The goal of this study was to assess the association between emotion regulation and different facets of impulsivity among patients with an alcohol use disorder and healthy controls. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
2
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 55 publications
4
56
2
7
Order By: Relevance
“…Similarly, the computer system of a car or plane can benefit from this architecture by detecting emotionally tense situations or negative emotions that are affecting the driver or the pilot and take preventive safety measures, such as stopping the car or informing the control tower [30,31]. As the emotional patterns can be used to determine different mental disorders [24][25][26] as well as physical diseases [27], the proposed architecture can be used for real-time monitoring and analysis of these patterns. The proposed architecture can also help people suffering from autism spectrum disorder (ASD) to better communicate with others and integrate into society [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the computer system of a car or plane can benefit from this architecture by detecting emotionally tense situations or negative emotions that are affecting the driver or the pilot and take preventive safety measures, such as stopping the car or informing the control tower [30,31]. As the emotional patterns can be used to determine different mental disorders [24][25][26] as well as physical diseases [27], the proposed architecture can be used for real-time monitoring and analysis of these patterns. The proposed architecture can also help people suffering from autism spectrum disorder (ASD) to better communicate with others and integrate into society [48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…The proposed SER system can be successfully used in HCI based on speech interaction, as well as integrated in computer-mediated education systems [47], for airplane or car accidents prevention [30,31], diagnosing mental disorders [24][25][26] and physical diseases [27], in call centers to improve the quality of customer service [22,23], and crime investigation departments by analyzing emotional patterns during suspect interrogations to find the perpetrator [28,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, we did not screen for impulsivity or common comorbidities such as impulse control disorders, which may be considered as a limitation. Because, as EDR [54,67], impulsivity is also regarded as an important feature of BPD [1,53,54], adult ADHD [27,54], and SUDs [58,67]. Similarly, we did not evaluate childhood trauma, which can be considered as a common etiological factor for the subjects of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have argued that individuals who have EDR are more likely to engage in addictive behaviours in an attempt to escape from, or minimize, negative moods and/or try alleviate distressing feelings [66]. A recent studies suggested that higher levels of difficulties regulating positive emotions were found to relate to greater alcohol and drug misuse [67,68]. EDR is a possible mechanism underlying the indirect relationship between negative affectivity and SUDs [69][70][71] and between early emotional and physical maltreatment and the development of SUDs [72].…”
mentioning
confidence: 99%